2005
DOI: 10.1118/1.2047807
|View full text |Cite
|
Sign up to set email alerts
|

Composition of MRI phantom equivalent to human tissues

Abstract: We previously developed two new MRI phantoms (called the CAG phantom and the CAGN phantom), with T1 and T2 relaxation times equivalent to those of any human tissue at 1.5 T. The conductivity of the CAGN phantom is equivalent to that of most types of human tissue in the frequency range of 1 to 130 MHz. In this paper, the relaxation times of human tissues are summarized, and the composition of the corresponding phantoms are provided in table form. The ingredients of these phantoms are carrageenan as the gelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 33 publications
0
77
0
1
Order By: Relevance
“…Similar to the materials stated above, carrageenan-based gel has been previously studied for its viability as an MRI phantom material. 1 The results demonstrated that by varying the concentrations of the carrageenan and the modifier, the values of T 1 and T 2 could be modified to match those of a human tissue. However, there has been no study to investigate the mechanical stability of the material, except a brief report on the fungal growth over time.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similar to the materials stated above, carrageenan-based gel has been previously studied for its viability as an MRI phantom material. 1 The results demonstrated that by varying the concentrations of the carrageenan and the modifier, the values of T 1 and T 2 could be modified to match those of a human tissue. However, there has been no study to investigate the mechanical stability of the material, except a brief report on the fungal growth over time.…”
Section: Introductionmentioning
confidence: 88%
“…The optimal characteristics of MRI phantoms used for such purposes are as follows: (1) relaxation times equivalent to those of human tissues, (2) dielectric properties equivalent to those of human tissues, (3) the relaxation times and dielectric properties should be homogeneous throughout the phantom, (4) mechanical properties suitable for fabrication of a human torso without the need for reinforcement, (5) can be used to form shapes of human organs, (6) ease of handling, and (7) stability of physical and imaging properties over an extended period. 1 Over the last few decades, several studies have been conducted on water-based polymer gels with paramagnetic ions as potential materials for MRI phantoms. Paramagnetic ions (i.e., CuSO 4 , NiCl 2 , MnCl 2 , and GdCl 3 ) are known to improve the visibility of internal body structures in MRI by altering the T 1 and T 2 relaxation times.…”
Section: Introductionmentioning
confidence: 99%
“…Phantoms of 2% (w/v) agar dissolved in nanopure (distilled and deionized) water, 0.01% (w/v) NaCl and various molar concentrations of gadopentetate dimeglumine (Gd-DTPA) were created in 50-mL centrifuge tubes. First, the agar powder was dissolved in 50 mL of nanopure water at 55-60 C and heated until 85 C for 5 min on a combined hotplate/magnetic stirrer until the solution became clear (19)(20)(21). Following the addition of NaCl, Gd-DTPA (MagnevistV R ) was then added at concentrations ranging from 0 to 2.0 mM (v/v) per tube to alter T 1 relaxivity and stirred for one minute.…”
Section: Tissue Modelmentioning
confidence: 99%
“…The results from images of these solutions also depend on the geometry of the container that holds them. Desirable characteristics for a DWI or DTI phantom are covering of a large range of diffusivities, long-term stability, low cost, low toxicity, T1 and T2 values similar to biological tissues, and high viscosity in order to minimize vibration and convective motions effects (Kato et al, 2005). Res.…”
Section: Mri Phantoms Described In Literaturementioning
confidence: 99%
“…There are phantoms of isotropic diffusion for DWI (typically spheres or cylinders filled by liquid) (Laubach et al, 1998;Lavdas et al, 2013;Pierpaoli et al, 2009); fiber phantoms to simulate axonal tracts or cardiac muscle (Fieremans et al, 2008;Lorenz et al, 2008;Teh et al, 2016); phantoms made of capillary or microcapillary arrays permeated by liquid with diffusion properties and/or relaxation times similar to biological tissues (Ebrahimi et al, 2010) test tubes with different solutions (Pierpaoli et al, 2009;Tofts et al, 2000); biological phantoms, such as green asparagus inside a water container (Latt et al, 2007); or animal tissues (axons of pigs or mice) (Chen et al, 2014;Komlosh et al, 2008). There are gels, for isotropic or anisotropic diffusion studies, whose magnetic properties are similar to healthy or pathological tissue (Hellerbach et al, 2013;Kato et al, 2005). Some authors propose applying the ACR MRI head phantom to evaluate scanner parameters related to degradation of DWI and DTI images, such as SNR, low contrast detectability and uniformity (Wang et al, 2011).…”
Section: Mri Phantoms Described In Literaturementioning
confidence: 99%